Adaptive low-power high-gain observers for lower-triangular systems with input-dependent Lipschitz constant. Issue 2 (2020) - Morfin, Elise; Astolfi, Daniele; Andrieu, Vincent
Abstract: We combine the low-power high-gain observer recently proposed in Astolfi and Marconi (2015) with the updated-gain technique used in Andrieu et al. (2009). The resulting adaptive low-power high-gain observer inherits the advantages of both techniques and can be used to address the state-estimation problem for Lipschitz systems in lower triangular form with nonlinearities having a Lipschitz constant that depends on a known external input.